The first Vietnam War : colonial conflict and cold war crisis - Lawrence, Mark Atwood; Logevall, Fredrik, 1963- (Harvard University Press, 2007)
In this work, scholars examine various dimensions of the struggle between France and Vietnamese revolutionaries that began in 1945 and reached its climax at Dien Bien Phu. Several essays break new ground in the study of the Vietnamese revolution and the establishment of the political and military apparatus that successfully challenged both France and the United States. Other essays explore the roles of China, France, Great Britain, and the United States, all of which contributed to the transformation of the conflict from a colonial skirmish to a Cold War crisis. --From publisher's description.